New Insights into the Nature of Co‐components and Their Impact on Pd Structure: X‐ray Absorption Studies on Toluene Acetoxylation Catalysts. Issue 43 (7th September 2015) - Gatla, Suresh; Radnik, Jörg; Madaan, Neetika; Pohl, Marga‐Martina; Mathon, Olivier; Rogalev, Andrei; Narayana Kalevaru, Venkata; Martin, Andreas; Pascarelli, Sakura; Brückner, Angelika
Abstract Co‐components are a powerful tool to tune the performance of catalysts, but their nature and their impact on the catalysts is often controversially discussed. In this study X‐ray absorption spectroscopy (XAS) was employed to elucidate the nature of co‐components and their impact on the catalytic reaction. In anatase‐supported Pd‐based catalysts for the gas‐phase acetoxylation of toluene, less noble co‐components (e.g., Mn, Co, and Sb) spread over the support in their oxidic form and changed their valence state on stream. Incorporated atoms such as C or a small part of the Sb affect the electronic structure of Pd. For the noble Au, only a weak interaction with the support and Pd was observed during time on stream. Only XAS at the K‐edges together with investigations of the Pd L‐edge for a better understanding of the electronic structure, supplemented by STEM for elemental mapping, allow such detailed insights.